Bacterial aetiology of pani sold with popular street food Chaat in Bengaluru - Vikyath Satish; PM Giridhara Upadhyaya; MS Kalpashree (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2021)
The primary focus of the study is to investigate the aetiology of the bacteria to bridge the gap between inadequate knowledge of bacterial growth in the pani and its role in food poisoning.  Aims and objectives: Isolation of bacteria in "pani" sold with popular street food chaat in Bengaluru  Identification of bacteria in "pani" sold with popular street food chaat in Bengaluru.  Procedure: 100 samples of pani purchased from the vendor in a parcel container was transferred to a sterile container of 30 mL capacity. The pani was streaked on MacConkey agar and Samonella Shigella agar and incubated at 37°centigrade overnight. After overnight incubation, the plates of agar were observed for growth. If growth was observed, the isolated colonies were taken up for identification by performing the requisite biochemical reactions. If growth was not observed after overnight incubation, the plates were further incubated for 24 hours. If no growth was observed even on Selenite F broth subcultured plates, the pani was considered sterile and free of aerobic bacteria.  Results: Of the 100 samples collected, growth of Non Lactose fermenters were reported in 12%; Lactose fermenters were 33% of which E.coli were 23% and Klebsiella were 14%; Enterococci were 16%; Suspected faecal contaminated samples were 51%; Candida were 39% and no growth was reported in 4% of samples. The above coliform bacteria indicate faecal contamination and pose a threat to humans health. Caution must be exercised to prevent the diseases caused by them. This health hazard was found in street stalls as well as in established restaurants which reflect the magnitude of disease risk in the community. Regularised food inspection should be conducted by Health Inspectors to determine and ensure compliance of food safety standards.  Conclusion: The isolation of the above mentioned organisms is unacceptable by the minimum standards of safe and wholesome drinking water and food safety standards. The isolated enteric bacteria play a role in food poisoning with high mortality and morbidity, particularly in developing nations, and avoidance of street vended food is key to its prevention.